Evaluation of the Accuracy of the Access Cavities Prepared by Undergraduate Dental Students at Tripoli University - Sumaya Aghila; Radya Shanaq; Mohamed Hshad; Mohamed Issa (Khalij-Libya Journal of Dental and Medical Research, 2025)
Access cavity efficiency is essential and a critical component of the clinical abilities needed for successful root canal treatment. It requires precise, professional hand skills, as well as a holistic cavity design based on radiographic interpretation and the clinical appearance of the accessible tooth. This study aimed to evaluate the quality of access cavity modalities performed by undergraduate dental students (n=73) at the Faculty of Dentistry, University of Tripoli. Students' access cavities, as well as the strengths and limitations of access cavity preparation in pri-clinic, were visually and radiographically assessed. The data were analyzed using descriptive statistics, frequencies, and percentages. Independent samples t-tests were used to compare the performance of male and female students in each of the parameters studied. The results indicated that students with relative skill in access and absence of overhangs received the highest score of 1.63 out of the evaluated features. Furthermore, the flaring score of 1.37 indicates a reasonable mastery of this aspect of the method. Nonetheless, the scores for Morphology (1.15) and Coronal Preservation (1.27) suggest areas that require further development and training. Undergraduate students demonstrate acceptable proficiency, particularly in achieving proper access and minimizing structural overhangs. However, the variation in scores for morphology and coronal root preservation indicates that these areas require further attention and need curricular enhancements and more targeted preclinical training to allow for full skill.